Using the Irrigation Controller for a Better Lawn on Less Water - Jack Tichenor; Michael D. Dukes; Laurie E. Trenholm (EDIS)
Would you like to have an attractive, healthy lawn that uses less water, costs less to maintain and may even reduce fertilizer and pesticide use? This may sound too good to be true. The right amount of water at the right time can make it happen for you. This document is Fact Sheet ENH978, one of a series of the Environmental Horticulture department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 23, 2003. Reviewed November 2004.